Effects Of Timing Prostaglandin F2α Injection Following Controlled Internal Drug Release Insert Removal On Oestrus Response, Follicular Dynamics And Pregnancy Rate In Nelore Cattle - Attia Hussein, Mohamed Ali (2008)
This research was conducted to evaluate the effect of oestrus synchronization protocol on oestrus response, follicular dynamics, pregnancy rate, and cortisol and progesterone concentrations in Nelore cattle under two types of handlings. In Experiment I (heavy handling), 27 cows were selected and subdivided into four groups, namely the Control G1, G2 and G3. The Control group (n= 8 cows) were treated with only CIDR inserts for 15 days. Meanwhile, G1 (n=5), G2 (n=6) and G3 (n=8) were treated with CIDR inserts for 15 days and given 500 μg of synthetic prostaglandin F2α at 9, 14 and 19 days post CIDR removal, respectively. Forty-eight hours after synchronization treatment, artificial insemination (AI) was done for cows that displayed oestrus, twice at 12 hours interval. Blood samples were collected two times per week on the day of CIDR insertion until after AI and continued for the next 30 days. Ultrasonographic examination was performed to determine follicle dynamic in four groups. In Experiment II (less handling), 30 cows were subdivided into four groups, Control group (n=7), G1 (n=9), G2 (n=6) and G3 (n=8). The protocol for all the four groups in Experiment II followed that of Experiment I, and the only difference was that blood samples were collected during and after AI, and at weekly intervals until the cows were confirmed to be pregnant by ultrasonography. There is no ultrasonographic examination to determine follicle dynamic in Experiment II. The proportion of cows observed in oestrus was higher in the Control group [62.5% and 100% in Experiments I and II, respectively (P<0.05)] than the other groups. The pregnancy rate was higher in G2 (16.6 % in Experiment I; 50 % in Experiment II) than in the other groups. However, the difference was not significant. The total numbers of cows displaying oestrus after treatment was significantly lower in Experiment I (11; 40.7 %) than Experiment II (20; 66.6 %). Similarly, the total number of pregnant cows was not significant in Experiment I (3; 11.1 %) and Experiment II (9; 30 %). There was a significantly difference (P<0.05) in the cows which did not display any oestrus after treatment between Experiment I (44.4 %) and Experiment II (13.3 %). The interval from treatment to the onset of oestrus and ovulation time (h) was highest (P<0.05) in G2 than other group. However, mean time from standing oestrus to ovulation (h) did not significant among groups. Mean size of dominant follicle at treatment and pre-ovulatory time was larger in control group (P<0.05) than other groups. Normal progesterone profile was evident in G1 (Experiment I and II), whereas the other groups showed abnormal progesterone profile throughout the oestrous cycle in both Experiment I and II. The total mean progesterone (P4) concentrations after AI were higher at Days 7 and 14 in Experiment II compared with Experiment I (P<0.05). The total mean cortisol concentration on the day of first AI, Days 7 and 13-14 post AI were higher in Experiment I than Experiment II but not significant (P<0.05). The results from this study showed a negative relationship between the progesterone and cortisol concentrations (r= -0.267, P<0.01) after first AI in Experiment I. In conclusion, luteal phase of the oestrous cycle and follicular development during the luteal phase may be considered as factors to affect the rate of oestrus synchronization in Nelore cattle. Variability in the interval to oestrus and the distribution of the oestrus response in cows that exhibited oestrus was due primarily to treating cows during the mid stage of the luteal phase (G2). The cause of this variability appears to be related to the manner in which progesterone decreased in cows during the mid stage of the luteal phase after PGF2α treatment and may also be related to ovarian follicular development. However, the greater degree of synchronization among animals was due to treatment with CIDR alone or together with administration of PGF2α 9 days after CIDR removal (G1). The results in the present study indicated that animals treated with PGF2α 9 days after CIDR treatment resulted in acceptable oestrus response and a single timed insemination gave acceptable pregnancy rates. In addition, Heavy handling may have altered the expression of oestrus, reduced the pregnancy rate and altered the progesterone profiles. On the other hand, less handling and gentle interaction with animal could improve the reproductive performance.